2018
DOI: 10.1159/000491532
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Memory CD8+ T Cell Differentiation by MicroRNAs

Abstract: MicroRNAs (miRNAs) have emerged as crucial regulators of T lymphocyte survival, differentiation and function, all of which are key factors impacting the outcome of adoptive T cell-based immunotherapy. It has become increasingly clear that the adoptive transfer of memory CD8+ T cell subsets is highly correlated with objective clinical responses for patients with advanced cancer. However, it is unclear how to improve the long-term persistence of transferred CD8+ T cells using miRNAs. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 88 publications
0
14
0
Order By: Relevance
“…Tsai et al (27) had reported that miR-155-deficient CD8 + T cells toward the development of memory cells. As CD8 + Tcm cells have been shown to confer superior immunity both in vitro and in vivo, it remains elusive whether manipulation of miR-155 expression in T cells may prove a useful way to generate preferential memory cells and lead to better immunotherapy (28). Recent study showed that the antitumor ability of CD8 + T has been limited by tumor-induced immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…Tsai et al (27) had reported that miR-155-deficient CD8 + T cells toward the development of memory cells. As CD8 + Tcm cells have been shown to confer superior immunity both in vitro and in vivo, it remains elusive whether manipulation of miR-155 expression in T cells may prove a useful way to generate preferential memory cells and lead to better immunotherapy (28). Recent study showed that the antitumor ability of CD8 + T has been limited by tumor-induced immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…Lots of reviews have described the important role of miRNAs in adaptive immunity (Dooley et al, 2013; Marques et al, 2015; Mehta and Baltimore, 2016; Zhang et al, 2018). miRNAs play an essential role in B-cell development and function, and one example of such is miR-181a-5p (Georgantas et al, 2007; Jensen et al, 2013).…”
Section: Epigenetic Regulation Of Genetic Programs In Immune Cellsmentioning
confidence: 99%
“…The role of mirnas in a variety of intracellular signaling processes, including those associated with tumors, has been verified (15,16). They are also involved in the regulation of gene expression at the transcriptional and post-transcriptional levels (17), and in the regulation of the cell cycle (18), cell proliferation (19,20), cell differentiation (21)…”
Section: Introductionmentioning
confidence: 98%